C13 Megastigmane Derivatives From Epipremnum pinnatum: β-Damascenone Inhibits the Expression of Pro-Inflammatory Cytokines and Leukocyte Adhesion Molecules as Well as NF-κB Signaling - Pan, San-Po; Pirker, Teresa; Kunert, Olaf; Kretschmer, Nadine; Hummelbrunner, Scarlet; Latkolik, Simone L.; Rappai, Julia; Dirsch, Verena M.; Bochkov, Valery; Bauer, Rudolf (Frontiers in Pharmacology, 2019)
In order to identify active constituents and to gain some information regarding their mode of action, extracts from leaves of Epipremnum pinnatum were tested for their ability to inhibit inflammatory gene expression in endothelial and monocyte-like cells (HUVEC and THP-1, respectively). Bioactivity-guided fractionation using expression of PTGS2 (COX-2) mRNA as a readout resulted in the isolation of two C13 megastigmane glycosides, gusanlungionoside C (1) and citroside A (3), and the phenylalcohol glycoside phenylmethyl-2-O-(6-O-rhamnosyl)-ß-D-galactopyranoside (2). Further analysis identified six additional megastigmane glycosides and the aglycones β-damascenone (10), megastigmatrienone (11), 3-hydroxy-β-damascenone (12) and 3-oxo-7,8-dihydro-α-ionol (13). Pharmacological analysis demonstrated that 10 inhibits LPS-stimulated induction of mRNAs encoding for proinflammatory cytokines and leukocyte adhesion molecules, such as TNFalpha, IL-1beta, IL-8, COX-2, E-selectin, ICAM-1, and VCAM-1 in HUVEC and THP-1 cells. 10 inhibited induction of inflammatory genes in HUVEC and THP-1 cells treated with different agonists such as TNFalpha, IL-1beta, and LPS. In addition to mRNA, also the upregulation of inflammatory proteins was inhibited by 10 as demonstrated by immune assays for cell surface E-selectin and secreted TNFalpha. Finally, using a luciferase reporter construct, it was shown, that 10 inhibits NFB-dependent transcription. Therefore, we hypothesize that inhibition of NFkB by β-damascenone (10) may represent one of the mechanisms underlying the in vitro anti-inflammatory activity of Epipremnum pinnatum extracts.